An approach to the broadband effect on Latin American growth: A structural model - Alderete, Maria Veronica (2017)
This paper analyses the fixed broadband penetration effect on Latin American economic growth. The methodology employed consists of using a simultaneous equation model based on Koutroumpis (2009) and Katz and Callorda (2013). To aid this process, we use country level data from the World Bank and the Regional Dialogue about the Information Society-DIRSI for the 2010-2014 period. The results obtained stress the importance of broadband penetration for economic growth in Latin America.